Changing plastid dynamics within early root and shoot apical meristem-derived tissue of A. thaliana - Bramham, Lawrence; Pyke, Kevin (Oxford University Press, 2017)
Whilst plastids are fundamental to many aspects of plant biology and the production of enhanced crop cultivars, research into the dynamics of non-green plastids has remained somewhat disregarded by the scientific community compared to chloroplasts. They are equally pivotal to normal plant development however, and are now increasingly becoming the focus of research made possible by genetic manipulation and reporter gene constructs.